Analysis of malathion and chlorpyrifos residues in juice, puree and fruit of mangoes using headspace-SPME with GC-MS - Mendoza, Rhodora Linda S. Manaloto (Animo Repository, 2006)
A study was conducted to investigate the applicability of Headspace Solid-Phase Microextraction (HSSPME) technique for the determination of malathion and chlorpyrifos residues in various mango products. Optimization procedures were also carried out to come up with the optimum parameters for the HSSPME technique. GCMS was used for the analysis. A headspace volume of 0.5 cm was employed during analyte extraction from the sample matrix to improve sensitivity. The PDMS 100µm fiber coating was chosen over PDMS/DVB 65µm for better detector response and reproducibility in analyzing malathion and chlorpyrifos. The optimum temperature and extraction time were observed to be 75°C and 45 minutes. A salt concentration of 30% (w/v) Na2SO4 was found to be suitable for increasing the detector response of both test compounds in GCMS. The best dilution volume varied among matrix, i.e., 50% dilution for puree, no further dilution (0%) for juice and 70% dilution for fruit samples were found effective. Results also gave indications that the sample matrix considerably affects recovery. For quantification studies, it was recommended that the external standard should be of matrix-matched calibration with that of the sample for analysis. It was observed that HSSPME in GCMS could be a valuable tool for a quick, accurate and reliable analytical method for determining chlorpyrifos and malathion residues in mangoes and mango-based products such as juice and puree. This was attested by the linearity of the response between actual concentration and detector response. Regression values were recorded, across all matrices, at 0.96 to 0.99. Based on all these, it was concluded that HSSPME in GCMS is suitable for use in OP pesticide residue analysis in mango and mango-based products.